From the Palace of Ryswick to the Sultan’s Seraglio: The Ottoman Translation and Interpretation of a Christian European Peace Treaty - Poulios, Konstantinos (Legatio: The Journal for Renaissance and Early Modern Diplomatic Studies, 2023)
The inclusion of peace treaty articles between Christian powers in an Ottoman historical work of the late seventeenth century is unquestionably distinctive. The article presents an Ottoman translation of the Treaty of Ryswick (1697) concluded between the French king and the German emperor. This translation is included by the late seventeenth – early eighteenth-century Ottoman historian and palace official Silāḥdār Fındıklılı Meḥmed Aġa in his historical work called ‘The Book of Victory’ (Nuṣretnāme). With this unique text as its basis, the article will first attempt to place the translation in its historical context and explain the possible reasons for its inclusion by Silahdar in his history. Secondly, to morphologically evaluate the text to bring to the fore the translation strategies adopted and to explore the reception and the degree of understanding by the Ottoman side of the basic terms and linguistic topoi of a Christian European peace treaty. And lastly, to analyse the specific interpretation ascribed to the Ryswick agreement by the Ottoman leadership.